Long-lived coupled peeling ballooning modes preceding ELMs on JET. (22nd March 2019) - Perez von Thun, C.; Frassinetti, L.; Horvath, L.; Saarelma, S.; Meneses, L.; de la Luna, E.; Beurskens, M.; Boom, J.; Flanagan, J.; Hillesheim, J.C.; Maggi, C.F.; Pamela, S.J.P.; et al.
Abstract: In some JET discharges, type-I edge localised modes (ELMs) are preceded by a class of low-frequency oscillations (Perez et al 2004 Nucl. Fusion 44 609). While in many cases the ELM is triggered during the growth phase of this oscillation, it is also observed that this type of oscillation can saturate and last for several tens of ms until an ELM occurs. In order to identify the nature of these modes, a wide pre-ELM oscillation database, including detailed pedestal profile information, has been assembled and analysed in terms of MHD stability parameters. The existence domain of these pre-ELM oscillations and the statistical distribution of toroidal mode numbers ( n ) up to n   =  16 have been mapped in ballooning alpha ( ) and either edge current density ( ) or pedestal collisionality ( ) coordinates and compared to linear MHD stability predictions. The pre-ELM oscillations are reliably observed when the ratio is high enough for the pedestal to access the coupled peeling-ballooning (PB) domain (aka stability nose). Conversely, when the pedestal is found to be in or near the high- n ballooning domain (which is at low ratio), ELMs are usually triggered promptly, i.e. with no detectable pre-ELM oscillations, or with pre-ELM oscillations only observable on ECE whose n appears to be too high to be resolved by the magnetics. Individual discharges can sometimes exhibit a fairly wide range of pre-ELM mode numbers, but for a wider database, the statistical n -number domains are found to be well ordered along the stability boundary and behave as expected from PB theory: the higher the ratio, the lower the mode's measured n tends to be. Within the measurement uncertainties, the measured n is usually found to be compatible with the most unstable n predicted by the linear stability code MISHKA1. These results confirm the earlier hypothesis that these modes are coupled peeling-ballooning modes, and extend and generalise to higher-mode numbers the work by Huysmans et al (1998 Nucl. Fusion 38 179), who identified the lowest n modes as pure external kink modes. Since the destabilisation of PB modes is widely accepted to give rise to ELMs, the mode saturation and delayed ELM triggering that is sometimes observed is rather unexpected. Possibilities to reconcile the extended lifetime of these modes with current ELM models are briefly discussed, but will require further investigation.